Electoral Regulation in Indonesia: Is It Modern Law? - Sholahuddin Al-Fatih (Unnes Law Journal, 2020)
This research tries to discuss modern law and its character which is elaborated through a review of Law No. 7 of 2017 on Elections. Through conceptual and statutory approaches, this research tries to examine the concept of modern law based on the benchmarks of ideas put forward by Max Webber, Marc Galenter and Charles Sampford.. The results of this study show that it is quite difficult to categorize the law in Indonesia as a modern law. Nevertheless, this research successfully shows that one of indonesia's legal products, Namely Law No. 7 of 2017 on Elections, has fulfilled elements of modern law. This research is expected to help academics and legal practitioners to be able to dig deeper into the concept of modern law so that it can be applied in law in Indonesia with some adaptation and adjustment.